2021
DOI: 10.3389/fonc.2020.616721
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Intelligence-Based Full-Process Solution for Radiotherapy: A Proof of Concept Study on Rectal Cancer

Abstract: Background and PurposeTo develop an artificial intelligence-based full-process solution for rectal cancer radiotherapy.Materials and MethodsA full-process solution that integrates autosegmentation and automatic treatment planning was developed under a single deep-learning framework. A convolutional neural network (CNN) was used to generate segmentations of the target and the organs at risk (OAR) as well as dose distribution. A script in Pinnacle that simulates the treatment planning process was used to execute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
(26 reference statements)
2
27
0
Order By: Relevance
“…Recently Xia et al [20] presented a proof-of-concept study for a similar AI-based planning approach for rectal cancer, where 80% of the automatically contoured and planned cases would have been accepted without manual fine-tuning for clinical treatment. Nevertheless, as demonstrated recently by McIntosh et al [15] acceptance of AI-based plans during a retrospective testing phase and a prospective phase may be different, where plans are intended to be used for clinical real-life treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Xia et al [20] presented a proof-of-concept study for a similar AI-based planning approach for rectal cancer, where 80% of the automatically contoured and planned cases would have been accepted without manual fine-tuning for clinical treatment. Nevertheless, as demonstrated recently by McIntosh et al [15] acceptance of AI-based plans during a retrospective testing phase and a prospective phase may be different, where plans are intended to be used for clinical real-life treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The full potential of automation in the RT treatment planning process would be exploited if the complete planning and data preparation workflow was automatized, including organ segmentation, CTV/PTV definition and treatment planning. Xia et al recently proposed full automation of the whole treatment preparation chain for rectal cancer [20]. We demonstrated clinical and technical feasibility of autonomous, un-supervised treatment plan-ning for MR-guided RT (MRgRT) of prostate cancer in a recent firstin-human application [21].…”
mentioning
confidence: 92%
“…This finding might have been caused by the algorithm difference between the two systems. Our system used a 2D U-Net network, which could have some outliers, as our previous study demonstrated [ 21 , 22 ]. UIH used a two-phase algorithm, which was more robust according to region location.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters which only fulfill tolerance are highlighted (criteria for penile bulb and CTVs are only used for evaluation during online adaption, but not during PSO). practice, but a similar workflow was recently proposed for rectal cancer [17] and automation of single processes was also introduced earlier [7][8][9][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Even though automation of certain steps in the data preparation and treatment planning process have been proposed earlier, currently each workflow step still requires human interaction for validation and further processing. Recently, a full automation of the entire process with integration of data handling and RT planning without any human interaction has been presented for rectal cancer [17]. Such autonomous, unsupervised data preparation and RT planning approach including OAR segmentation, target volume definition and plan optimization may have the potential to harmonize treatments and reduce the time from simulation to RT start.…”
mentioning
confidence: 99%